2003
DOI: 10.1525/sop.2003.46.2.149
|View full text |Cite
|
Sign up to set email alerts
|

To Snitch or Not to Snitch? Applying the Concept of Neutralization Techniques to the Enforcement of Occupational Misconduct

Abstract: The controversy over self-regulation has been a central topic of inquiry in sociological research on occupational misconduct and crime. However, few studies have examined the process by which organizational members decide whether to respond to the misconduct of peers, and none have examined the use of neutralization techniques by rule enforcers in organizational settings. The research presented here is based on a case study of the U.S. Naval Academy. Three data sources are analyzed: Survey data collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…(Miceli & Near, 2006), "Do I tell or do I not tell?" (Berry, 2004), or "Do I snitch or do I not snitch" (Pershing, 2003). When employees refrain from taking action, they become "inactive observers" (Miceli & Near, 1992) or "silent observers" (Rothschild & Miethe, 1999), which is undesirable when the norm is to prevent, detect and correct wrongdoing (Miceli et al, 2008).…”
Section: Hypotheses Responses To Observed Wrongdoingmentioning
confidence: 99%
“…(Miceli & Near, 2006), "Do I tell or do I not tell?" (Berry, 2004), or "Do I snitch or do I not snitch" (Pershing, 2003). When employees refrain from taking action, they become "inactive observers" (Miceli & Near, 1992) or "silent observers" (Rothschild & Miethe, 1999), which is undesirable when the norm is to prevent, detect and correct wrongdoing (Miceli et al, 2008).…”
Section: Hypotheses Responses To Observed Wrongdoingmentioning
confidence: 99%
“…Levi, 1981;Eliason and Dodder, 1999;Fox, 1999). It has also been the subject of more intuitive applications including the victimisation of battered wives (Ferraro and Johnson, 1983), genocide and the Holocaust (Alvarez, 1997), organisational rule enforcing (Fershing, 2003) and the management of the ''temporary deviant'' label of pageant mothers in the United States (Heltsley and Calhoun, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…New employees shed their probationary status after they proved their solidarity with established employees by obeying and enforcing the rules (Barker, 1993). Moreover, although whistle-blowing is often considered a prosocial behavior (Brief and Motowidlo, 1986;Dozier and Miceli, 1985;Near, 1988, 1992), failure to blow the whistle on misbehavior is often construed as complicity in the deviance (Pershing, 2003;Treviño and Victor, 1992). Therefore, we expect to find that perceptions of informal prosocial control positively predict whistleblowing.…”
Section: Whistle-blowing As Concertive Controlmentioning
confidence: 95%
“…Criminologists have found that most varieties of deviant behavior peak in late adolescence, and slowly decline thereafter, although the causes of this decline are debated (Ezell and Cohen, 2005). Failure to report unethical behavior to organizational authorities is often officially or unofficially considered complicity in that behavior, howsoever common such complicity may be (Pershing, 2003;Treviño and Victor, 1992), so it is not unreasonable to suspect that nonreporting would be higher for the youngest employees along with other forms of deviance.…”
mentioning
confidence: 99%